PENGEMBANGAN SISTEM INFORMASI INVENTARIS ALAT-ALAT LABORATORIUM JURUSAN PENDIDIKAN FISIKA BERBASIS WEB - I Nyoman Putu Suwindra; Iwan Suswandi; I G. A. N. Sri Wahyuni; Kadek Surya Mahedy (Jurnal Pendidikan Fisika Undiksha, 2023)
The development of the information system in this study aims to inventory laboratory equipment for the Department of Physics Education, Faculty of Mathematics and Natural Sciences, University of Education, Ganesha. This information system is expected to facilitate information services about the whereabouts and condition of Physics laboratory equipment quickly, easily and precisely which can be accessed online. This research method is the Water Fall model with the steps: Engineering system, Analysing, Designing, Coding, Testing, and Maintenance. The results achieved include: (1) A web-based Inventory Information System with several features including: The system's main menu consists of: Home, Master Data, Inventory Entry Lab, Administration, Inventory Lab Reports, and Admin; (2) The results of system testing show that the system is running well without any bugs, especially in terms of creating master data and inputting data; (3) The process of inputting laboratory equipment data has been carried out in stages starting from basic physics laboratory equipment; (4) The system can be accessed online, especially by students as users; (5) the system needs to be updated on the login page so that users and administrators have different privileges. Keywords: information system, inventory, equipment of physics laboratory